1998
DOI: 10.1212/wnl.51.6.1746
|View full text |Cite
|
Sign up to set email alerts
|

The first European family with tibial muscular dystrophy outside the Finnish population

Abstract: We report the first European tibial muscular dystrophy (TMD) family outside the Finnish population. Clinical examination showed late onset distal leg myopathy similar to the description of TMD. A molecular genetic study was made owing to the very recent TMD linkage findings on chromosome 2q31. All five clinically affected patients segregated a specific haplotype for the locus, whereas two unaffected patients had different haplotype. The results of this family without Finnish ancestors show that TMD exists outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…This founder mutation is called FINmaj and it consists of an 11-bp deletion/insertion mutation that changes four amino acid residues [12]. Other mutations were later identified in families from different European populations, such as in French [3] and Belgian populations [4], and recently two new mutations in different parts of France and one new mutation in two families from Spain [5] (Table 1). Homozygous TMD causing mutations in the titin gene cause the more severe limb-girdle muscular dystrophy type 2J (LGMD2J) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This founder mutation is called FINmaj and it consists of an 11-bp deletion/insertion mutation that changes four amino acid residues [12]. Other mutations were later identified in families from different European populations, such as in French [3] and Belgian populations [4], and recently two new mutations in different parts of France and one new mutation in two families from Spain [5] (Table 1). Homozygous TMD causing mutations in the titin gene cause the more severe limb-girdle muscular dystrophy type 2J (LGMD2J) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, it was described also in French [3] and Belgian families [4]. Recently Hackman et al have identified three new mutations in families from Spain and France [5].…”
Section: Introductionmentioning
confidence: 96%
“…Some recent articles reporting rimmed vacuoles also describe 15-19-nm cytoplasmic and nuclear filaments, seen on electron microscopy. 22,63 Such filaments can be found in a number of other myopathies, such as inclusion-body myositis (IBM), and are not specific for any particular disorder ( 30,70,107,113,116 This group shares a distinct clinical phenotype, comprising weakness beginning in the anterior compartment of the legs, and is often referred to as tibial muscular dystrophy. Symptoms begin after age 40 years.…”
Section: Hereditary Distal Myopathiesmentioning
confidence: 99%
“…A French family with progressive anterior tibial weakness and atrophy beginning in the fifth to sixth decades has also been linked to the 2q31 locus. 30 Titin (connectin) is a possible candidate gene for this disorder. 112 Titin is a large protein present in vertebral striated muscle cells that appears to play important roles in sarcomere assembly and integrity.…”
Section: Hereditary Distal Myopathiesmentioning
confidence: 99%
“…Moreover severe myopathy with lethal cardiomyopathy and recessive congenital myopathy were shown to be titinopathies [12][13][14]. Several reports have described TMD in patients outside Finland [15][16][17][18], and recently atypical phenotypes in patients with FINmaj mutation were reported to have a second TTN mutation in compound heterozygosity [19].…”
Section: Introductionmentioning
confidence: 99%